2005
DOI: 10.1007/s10265-004-0190-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of jasmonic acid and its methyl ester as gum-inducing factors in tulips

Abstract: The purpose of this study was to identify endogenous factors that induce gummosis and to show their role in gummosis in tulip (Tulipa gesneriana L. cv. Apeldoorn) stems. Using procedures to detect endogenous factors that induce gum in the stem of tulips, jasmonic acid (JA) and methyl jasmonate (JA-Me) were successfully identified using gas-liquid chromatography-mass spectrometry. Total amounts of JA and JA-Me designated as jasmonates in tulip stems were also estimated at about 70-80 ng/g fresh weight, using de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…In tulip stems, gum formation was not induced by ethephon treatment but by treatment with jasmonic acid and JA-Me (Skrzypek et al, 2005). Saniewski et al (2006) suggested that gum formation might be coregulated by the ratio of the relative concentration of ethylene and jasmonates; however, our results suggest that JA-Me, not ethylene, induces gum accumulation in Japanese apricot fruit (Table 2).…”
Section: Treatment Of Chemicalscontrasting
confidence: 72%
“…In tulip stems, gum formation was not induced by ethephon treatment but by treatment with jasmonic acid and JA-Me (Skrzypek et al, 2005). Saniewski et al (2006) suggested that gum formation might be coregulated by the ratio of the relative concentration of ethylene and jasmonates; however, our results suggest that JA-Me, not ethylene, induces gum accumulation in Japanese apricot fruit (Table 2).…”
Section: Treatment Of Chemicalscontrasting
confidence: 72%
“…On the other hand, JA acting synergistically with the ET-releasing compound ethephon has been found to induce gummosis in tulips (Skrzypek et al, 2005), suggesting a similar induction cascade. The synergistic effect of ACC and JA applied simultaneously to plants cannot be attributed to increased concentrations of these compounds in the stem tissues, as we were expecting based on reports of positive interactions between jasmonates and ET biosynthesis (Yu et al, 2009).…”
Section: Roles Of Jasmonates and Ethylene In Induction Of Tylosesmentioning
confidence: 99%
“…The application of ET in tulip bulbs leads to gum formation, and the effect can be prevented through pretreatment with the ET receptor inhibitor 1-methylcyclopropane (1-MCP) (de Wild et al, 2002 ). JA can induce gummosis in tulip (Skrzypek et al, 2005a , b ) and grape hyacinth (Miyamoto et al, 2010 ), as well as in various species of stone-fruit trees such as plum shoots and fruits (Saniewski et al, 2002 ), apricot (Saniewski et al, 2001 ), and peach shoots (Saniewski et al, 1998 ; Li et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%